Psychometric properties of the New General Self-Efficacy Scale for Vietnamese persons with colorectal cancer - Tran Thi Hong Hanh; Sureeporn Thanasilp; Noppamat Pudtong (Belitung Raya Foundation, 2024)
Background: There are currently no specific tools available to assess self-efficacy among Vietnamese individuals with colorectal cancer (CRC) post-surgery. Translating and evaluating the psychometric properties of the New General Self-Efficacy Scale (NGSE) for use in the Vietnamese population could help address this gap. Objective: This study aimed to evaluate the psychometric properties of the Vietnamese version of the NGSE scale. Methods: A cross-sectional study was conducted. The sample consisted of 120 individuals aged 20-59 with CRC post-surgery, recruited through a multi-stage sampling technique from three hospitals in Vietnam. The scale was translated into Vietnamese using Brislin's technique. Content validity was assessed using the Content Validity Index for item (I-CVI) and for scale (S-CVI). Construct validity was examined through confirmatory factor analysis (CFA), and reliability was measured using Cronbach's α coefficients. Results: The findings showed an I-CVI of 1.00 and an S-CVI of 1.00, indicating excellent content validity. The Cronbach's α for the NGSE was 0.95, indicating excellent internal consistency. CFA results showed that all eight items fit well within a unidimensional structure (X2 = 48.936, p >0.05, df = 24, X2/df = 2.04, RMSEA = 0.078, CFI = 0.979, TLI = 0.971, SRMR = 0.023). Factor loadings for each item ranged from 0.798 to 0.901. Conclusion: The results suggest that the NGSE scale demonstrates good psychometric properties as applied to the Vietnamese individuals examined in this study. This instrument can be regularly utilized in clinical settings to identify key concerns in colorectal cancer patients' care and facilitate appropriate nursing interventions to enhance self-efficacy in this population effectively.